2020
DOI: 10.1002/solr.202000455
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Control of Methylammonium‐Free Perovskite in Two‐Step Deposited Printable Triple‐Mesoscopic Solar Cells

Abstract: The evolution from the original methylammonium (MA)‐ to formamidinium (FA)‐dominated perovskite makes a crucial contribution to improve the photoelectric performance of perovskite solar cells (PSCs) in a decade. However, to obtain α‐FAPbI3, annealing temperature above 100 °C is essential. In addition, it is still challenging to deposit a uniform and high‐quality FA‐based perovskite absorber in printable triple‐mesoscopic PSC due to the complicated mesoscopic structure. Herein, a low‐temperature, two‐step seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 45 publications
1
33
0
1
Order By: Relevance
“…By tuning the composition and crystallization of perovskite absorbers in the mesoporous scaffold, [ 13–15 ] modifying the mesoporous scaffold and interfaces [ 16,17 ] and developing novel deposition technique, [ 14 ] the efficiency of triple‐mesoscopic PSCs has been improved from the initial 6% to current 16.51%. [ 9,16,18,19 ] Particularly, the devices have been suffering severe potential loss, and thus showed low open‐circuit voltage ( V OC , 0.85–0.95 V). In one hand, the mesoporous scaffold is micrometer‐thick, which determines the charge diffusion length in the device.…”
Section: Introductionmentioning
confidence: 99%
“…By tuning the composition and crystallization of perovskite absorbers in the mesoporous scaffold, [ 13–15 ] modifying the mesoporous scaffold and interfaces [ 16,17 ] and developing novel deposition technique, [ 14 ] the efficiency of triple‐mesoscopic PSCs has been improved from the initial 6% to current 16.51%. [ 9,16,18,19 ] Particularly, the devices have been suffering severe potential loss, and thus showed low open‐circuit voltage ( V OC , 0.85–0.95 V). In one hand, the mesoporous scaffold is micrometer‐thick, which determines the charge diffusion length in the device.…”
Section: Introductionmentioning
confidence: 99%
“…
Nevertheless, the efficiency of the printable mesoscopic PSCs still lags behind the conventional PSCs. Though extensive methods have been conducted to improve the performance of such devices, including additives, [12][13][14][15][16] composition engineering, [17,18] and crystallization control, [18][19][20] the highest PCE reported so far is 18.2% using an acetamidinium mixed methylammonium lead iodide perovskite. [21] In the meantime, though FAPbI 3 perovskites are believed and reported to yield higher PCEs, we only achieved a PCE of ≈16% using FAPbI 3 perovskite.
…”
mentioning
confidence: 99%
“…During the film formation process, strong interaction between Acand Pb 2+ plays a significant role in the improved quality of resulting perovskite films. Moreover, various previous reports have confirmed that Ac -(in form of PbAc 2, FAAc, MAAc) is engaged in the perovskite growth process, leading to larger grains, and reducing defects [35][36][37] .…”
Section: Introductionmentioning
confidence: 73%